178k views
4 votes
Solve the following by substitution
2x - 3y = -6
-5x - 9y = 15

User Jhaagsma
by
5.3k points

1 Answer

6 votes

Answer:

x=-3, y=0. (-3, 0).

Explanation:

2x-3y=-6

-5x-9y=15

---------------

-3(2x-3y)=-3(-6)

-5x-9y=15

----------------------

-6x+9y=18

-5x-9y=15

--------------

-11x=33

x=33/-11=-3

2(-3)-3y=-6

-6-3y=-6

3y=-6-(-6)

3y=-6+6

3y=0

y=0/3=0

User TTransmit
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.